Analisis Persentase Sedimentasi Dan Dampaknya Terhadap Debit Aliran Pada Penampang Saluran Trapesium Dan Persegi - Azka Ikrimah Ahmad; Tiara Revitasari; Yuni Yolanda (CV. SINAR HOWUHOWU, 2026)
Analysis of Sedimentation Percentage and Its Impact on Flow Discharge in Trapezoidal and Rectangular Channel Sections. Sedimentation in drainage channels is a major cause of reduced capacity and flow effectiveness. This study aims to analyze the effect of sedimentation percentage on flow discharge in five segments of drainage channels with variations in cross-section types (rectangular and trapezoidal) and dimensions. The data used include top width, bottom width, channel height, sediment thickness, and water surface height in each segment. The analysis was conducted using Manning’s equation to calculate the actual flow discharge under existing conditions. The results show that the highest sedimentation levels occur in Segments 2 and 3, with percentages of 20.8% and actual discharges of 0.597 m³/s and 0.560 m³/s, respectively. Segment 1 with a trapezoidal section has 7.4% sedimentation and the smallest discharge of 0.0022 m³/s due to small channel dimensions. Segments 4 and 5 have sedimentation rates of 7.5% and 4.6% with actual discharges of 0.0278 m³/s and 0.0286 m³/s. It can be concluded that sedimentation significantly affects the reduction of flow discharge, and rectangular sections with adequate dimensions provide better flow capacity compared to trapezoidal sections with small dimensions.